2016
DOI: 10.5693/djo.01.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of presumed, noninfectious endophthalmitis after intravitreal injection of bevacizumab: long-term follow-up

Abstract: Purpose-To report the outcome of 5 consecutive cases of presumed, noninfectious endopththalmitis following intravitreal injection of bevacizumab (IVB).Methods-Ten pre-loaded syringes of bevacizumab (1.25 mg/50 µL) furnished by a compounding pharmacy were injected intravitreally. Treatments were performed in the operating room by the same surgeon on 2 consecutive days.Results-Of 10 eyes, 5 showed moderate to severe ocular inflammation within a few days of injection. All patients were treated in the same surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Also, ziv-aflibercept, an anti-VEGF drug approved for treating colorectal cancer, has been investigated as a treatment for nAMD [37], despite the fact that in the EU intravitreal use of ziv-aflibercept is contraindicated because of its hyperosmotic properties [38]. In addition to their off-labeldriven limitations, both products require additional compounding prior to use in retinal diseases, which may increase the risk of intraocular infections [39][40][41][42].…”
Section: What Role May Biosimilars Play In the Ophthalmology Space?mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, ziv-aflibercept, an anti-VEGF drug approved for treating colorectal cancer, has been investigated as a treatment for nAMD [37], despite the fact that in the EU intravitreal use of ziv-aflibercept is contraindicated because of its hyperosmotic properties [38]. In addition to their off-labeldriven limitations, both products require additional compounding prior to use in retinal diseases, which may increase the risk of intraocular infections [39][40][41][42].…”
Section: What Role May Biosimilars Play In the Ophthalmology Space?mentioning
confidence: 99%
“…Some physicians may query why they should use biosimilars when payers will reimburse reference products, or when bevacizumab or zivaflibercept is available to them. The fact that the use of both bevacizumab and ziv-aflibercept in ophthalmology is off-label, together with concerns regarding inflammation and infection following intravitreal administration of both products, may create a sense of uncertainty with prescribers [39][40][41][42]126]. Furthermore, the use of bevacizumab is not available in all countries, or even uniformly within countries, reflecting diverging opinions of governments and clinical societies on its use [127].…”
Section: Practical Guide For the Use Of Biosimilarsmentioning
confidence: 99%
“…Given the fact that the vitreous is a small, contained space and that neovascular retinal diseases typically require ongoing treatment, the risks associated with injecting particulate matter (including silicone oil) into the vitreous may be cumulative, 4 , 5 and particles may have association with complications such as floaters, sustained increase in intraocular pressure, and endophthalmitis. 6 9 …”
mentioning
confidence: 99%
“…Given the fact that the vitreous is a small, contained space and that neovascular retinal diseases typically require ongoing treatment, the risks associated with injecting particulate matter (including silicone oil) into the vitreous may be cumulative, 4,5 and particles may have association with complications such as floaters, sustained increase in intraocular pressure, and endophthalmitis. [6][7][8][9] On-label injectable drug products are required, according to United States Pharmacopeia chapter ,790., to be "essentially free" of visible particles and USP ,789. strictly limits subvisible particles in ophthalmic solutions. However, USP ,789. is subject to interpretation.…”
mentioning
confidence: 99%
“…The cases include patients invoking immune reaction to the biological drug itself, an entity known as anti-drug antibody; or reaction to the impurities present in the drug formulation [6]. There have been several reports of cluster sterile endophthalmitis arising from intravitreal bevacizumab therapy [7][8][9]. Wang et al reported cluster of sterile endophthalmitis (69%) due to counterfeit bevacizumab.…”
mentioning
confidence: 99%